SMART ELECTRICITY THEFT ESTIMATION USING ANDROID - Sai Aravind, K.B.; J., Mohana (International Journal of Psychosocial Rehabilitation, 2020)
In this paper, we implement a system that calculates the unit of current consumption through the unit of current and voltage sensors. The sensor is mounted in the EB meter. This paper proposes the smart energy meter with reading indicator using IoT built to decrease the bill for power consumption by providing the consumer with a warning message for the energy meter reading before raising the unit charge. We can get current consumption by gaining the sensor value. Upon receiving current consumption, the unit given to a specific user will be that by Arduino UNO. The unit is known as a numerical value. This will inform the user via IoT module and Android Mobile if the device is reduced to a minimum value. If the user wants to add more units to the EB list, he / she must send a message. The required value is sent to the Arduino controller via IoT modem from the EB section. The Arduino UNO will increase the unit in the memory from the value obtained. Thus, the process of recharging is done quickly with fewer manual interactions. Our system can be used for industrial control, medical systems, and management of access. Live meter readings from the energy meter activated by IoT are regularly forwarded back to this billing point, and this information is stored in a database. The customer can also monitor the electricity status from anywhere. It makes the measurement readings easy to take with precision.